An overview of focal approaches of critical discourse analysis - Jahedi, Maryam; Abdullah, Mohd Faiz Sathivellu; Mukundan, Jayakaran (Australian International Academic Centre, 2014)
This article aims to present detailed accounts of central approaches to Critical Discourse Analysis. It focuses on the work of three prominent scholars such as Fairclough’s critical approach, Wodak’s discourse-historical approach and Van Dijk’s socio-cognitive approach. This study concludes that a combination of these three approaches can be useful to critical analysis of texts.